1994
DOI: 10.1017/s0950268800051578
|View full text |Cite
|
Sign up to set email alerts
|

Identification of astrovirus serotypes from children treated at the Hospitals for Sick Children, London 1981–93

Abstract: SUMMARYAn enzyme immunoassay (EIA) for astrovirus type 1 together with immune electronmicroscopy (IEM) was used to type a collection of 162 astroviruses obtained from 1981-93 from children with diarrhoea. The EIA was found to be specific for astrovirus type 1. Astrovirus types 2-4 were typed by IEM.Astrovirus type 1 was the prevalent serotype 107/125 (86 %), followed by type 3 (8 %), type 4 (6 %) and type 2 (1 %). Six samples containing astrovirus could not be typed or detected by EIA because they were coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…As in many worldwide studies, a previous pediatrician-based study conducted from 1995 to 1998 (3) showed that type 1 was predominant (9 out of the 10 strains; unpublished data). The diversity described in the present investigation may have been due to the fact that all age groups were tested, whereas most studies reporting type1 predominance were conducted with young children (9,26,29,32). Here, six of the eight strains detected were found in patients more than 3 years old, and both of the astroviruses detected in on May 9, 2018 by guest http://jcm.asm.org/ young children were not type 1 but were types 4 and 8.…”
Section: Discussionmentioning
confidence: 78%
“…As in many worldwide studies, a previous pediatrician-based study conducted from 1995 to 1998 (3) showed that type 1 was predominant (9 out of the 10 strains; unpublished data). The diversity described in the present investigation may have been due to the fact that all age groups were tested, whereas most studies reporting type1 predominance were conducted with young children (9,26,29,32). Here, six of the eight strains detected were found in patients more than 3 years old, and both of the astroviruses detected in on May 9, 2018 by guest http://jcm.asm.org/ young children were not type 1 but were types 4 and 8.…”
Section: Discussionmentioning
confidence: 78%
“…In the past, HAstVs were routinely detected by direct transmission electron microscopy (EM) in negatively stained stool The use of antibodies in immune electron microscopy (IEM) or solid-phase immune electron microscopy (SPIEM) enhances the sensitivity of the assay while enabling confirmation of the identity of the viral agent (88,207,252,271). However, the limited availability of antibodies for the different HAstV types hampers the use of these techniques (34).…”
Section: Laboratory Diagnostics Early Developments: Electron Microscomentioning
confidence: 99%
“…Traditionally, astroviruses have been diagnosed by electron microscopy (19,20,26), more recently replaced in many laboratories by in-house enzyme immunoassays (15,26,27) and more recently commercial enzyme immunoassays (22).…”
Section: An Outbreak Of Astrovirus Gastroenteritis Occurred In the Prmentioning
confidence: 99%